2022
DOI: 10.3390/ma15248791
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of c- and m-Plane AlN Seeds Grown by Physical Vapor Transport

Abstract: The ultra-wide bandgap semiconductor AlN has attracted a great deal of attention owing to its wide application potential in the field of electronics and optoelectronic devices. In this report, based on the mechanism of the physical vapor transport (PVT) growth of AlN crystal, the c- and m-plane AlN seed crystals were prepared simultaneously through special temperature field design. It is proved that AlN crystals with different orientations can be obtained at the same temperature field. The structure parameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…4 (670.8 and 657.4 cm −1 ) are the phonon frequencies of E 1 (TO) and E 2 (high) for strain-free AlN, respectively. [34][35][36] Here, we extracted the E 1 (TO) and E 2 (high) peak positions of all the a-AlN samples from the Raman curves in Fig. 4 1 and Table 1, it can be found that the blue-shift of the Raman peaks increases with the decreasing BSFD, which means that the compressive stress was accumulated with the decrease in BSFD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 (670.8 and 657.4 cm −1 ) are the phonon frequencies of E 1 (TO) and E 2 (high) for strain-free AlN, respectively. [34][35][36] Here, we extracted the E 1 (TO) and E 2 (high) peak positions of all the a-AlN samples from the Raman curves in Fig. 4 1 and Table 1, it can be found that the blue-shift of the Raman peaks increases with the decreasing BSFD, which means that the compressive stress was accumulated with the decrease in BSFD.…”
Section: Resultsmentioning
confidence: 99%
“…4 (670.8 and 657.4 cm −1 ) are the phonon frequencies of E 1 (TO) and E 2 (high) for strain-free AlN, respectively. 34–36 Here, we extracted the E 1 (TO) and E 2 (high) peak positions of all the a -AlN samples from the Raman curves in Fig. 4(a) and (c), and the results are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods have been tried to prepare AlN single crystals, including hydride vapor phase epitaxy (HVPE), 11 the ammonothermal method, 12 molecular beam epitaxy (MBE), 13 metal-organic chemical vapor deposition (MOCVD), 14 and physical vapor phase transport (PVT). 15,16 Among them, PVT is the most successful method for preparing high-quality and large-size AlN single crystals. However, the PVT method still faces many challenges in experiments, such as a limited growth environment, high growth temperature of up to 2000-2300 °C, long growth period, and high degree of stability and control accuracy in the temperature field.…”
Section: Introductionmentioning
confidence: 99%